2024
DOI: 10.1007/s00253-023-12953-y
|View full text |Cite
|
Sign up to set email alerts
|

Potassium sodium hydrogen citrate intervention on gut microbiota and clinical features in uric acid stone patients

Cheng Cao,
Feng Li,
Qi Ding
et al.

Abstract: The high recurrence rate of renal uric acid stone (UAS) poses a significant challenge for urologists, and potassium sodium hydrogen citrate (PSHC) has been proven to be an effective oral dissolution drug. However, no studies have investigated the impact of PSHC on gut microbiota and its metabolites during stone dissolution therapy. We prospectively recruited 37 UAS patients and 40 healthy subjects, of which 12 patients completed a 3-month pharmacological intervention. Fasting vein blood was extracted and mid-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…[ 22 ]. Studies have shown that a set of conserved genes widely present in uric-acid-consuming Enterobacteriaceae encode the uric acid degradation pathway, converting uric acid to SCFAs [ 43 ]. There have also been studies that have shown that propionic acid and butyric acid [ 44 ] are among the SCFAs that provide ATP to the cells of the intestinal wall, which excretes uric acid [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ]. Studies have shown that a set of conserved genes widely present in uric-acid-consuming Enterobacteriaceae encode the uric acid degradation pathway, converting uric acid to SCFAs [ 43 ]. There have also been studies that have shown that propionic acid and butyric acid [ 44 ] are among the SCFAs that provide ATP to the cells of the intestinal wall, which excretes uric acid [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ileibacterium has previously been linked to metabolic disorders and intestinal inflammation ( Gao X. et al, 2021 ; Lin et al, 2022 ). However, some studies have shown that Ileibacterium and Parasutterella are positively correlated with butyric acid production ( Huang et al, 2023 ; Cao et al, 2024 ). In the present study, the abundance of Ileibacterium and Parasutterella in the Ctrl group was significantly lower than that in the DSS group.…”
Section: Discussionmentioning
confidence: 99%